Pola Komunikasi Organisasi Cuatrodia Creative - Luthfi Algi Fari; Wiki Angga Wiksana (UNISBA Press, 2023)
Abstract. A production house is a part of a person or individual who produces a media content. the importance of conveying information clearly makes communication effective, where in organizational communication there is someone who must be able to lead an organization. Carry out the vision and mission of an organization. Therefore, leaders must be able to convey information or communicate very well and can be understood by their members.The purpose of this research is (1) to determine the communication pattern of Cuatrodia creative organization (2) to find out the factors that hinder the improvement of the animation quality of Cuatrodia creative Production House.This research is a qualitative type of research with a case study approach with the title “Catrodia creative organizational communication pattern case study on supervisors and internship members in improving the quality of animation at the Ministry of Education and Culture. Data collection techniques used in this study were through interviews, documentation, literature study and direct observation.he results of the research from the Cuatrodia creative organizational communication pattern in improving the quality of animated videos of the Ministry of Education and Culture, namely (1) the organizational structure of creative cuatrodia is clear and structured, (2) the communication pattern used by the wheel pattern leader (Wheell Network), (3) the leadership style of creative cuatrodia Directive style, (4) Many internship members are WFH (Work From Home), (5) leaders are less close to their subordinates due to WFH factors, (6) leaders are more likely to make their own decisions (7) Internship members do not manage time well, resulting in delays workmanship becomes a barrier in improving the quality of animation. Abstrak. Rumah produksi ( Production House ) merupakan bagian dai orang atau individu yang meproduksi sebuah konten media. pentingnya menyampaikan infomasi secara jelas menjadikan komunikasi menjadi efektif, dimana dalam komunikasi organisasi terdapat seseorang yang harus mampu memimpin sebuah organisasi. Menjalankan visi dan misi dari suatu organisasi. Oleh karena itu pemimpin harus bisa menyampaikan informasi ataupun berkomunikasi dengan sangat baik dan dapat dipahami oleh anggotanya.Tujuan dari penelitian ini adalah (1) untuk mengetahui pola komunikasi organisasi Cuatrodia creative (2) untuk mengetahui faktor-faktor yang menghambat peningkatan kualitas animasi Production House Cuatrodia creative. Penelitian ini adalah penelitian jenis kualitatif dengan pendekatan studi kasus dengan judul Pola komunikasi organisasi cuatrodia creative studi kasus pada atasan dan anggota internship dalam meningkatkan kualitas animasi kemendikbud. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah melalui wawancaa, dokumentasi, studi pustaka dan pengamatan langsung.. Hasil dari penelitian dari Pola komunikasi organisasi Cuatrodia creative dalam meningkatkan kualitas video animasi kemendikbud, yaitu (1) struktur organisasi cuatrodia creative jelas dan tersetruktur, (2) Pola komunikasi yang digunakan pimpinan pola roda (Wheell Network), (3) Gaya kepemimpinan cuatrodia creative Directive style , (4) Banyak anggota internship yang WFH (Work From Home), (5) pemimpin kurang dekat dengan bawahan karena faktor WFH, (6) pemimpin lebih cenderung mengambil keputusannya sendiri (7) anggota internship kurang memanage waktu dengan baik sehingga keterlambatan pengerjaan menjadi penghalang dalam peningkatan kualitas animasi.